THE PROPHETS VISION MOHAMMED (peace be upon him) to His GOD at NIGHT of MIRAGE HAPPENING In AHADITH ALSAHIHAEEN (Nagative and Correct) - Ahmed , Hussain (Islamic Sciences Journal, 2023)
The scholars are unanimously agreed that the prophet Mohammed (peace and blessings of Allah be upon him) was taken to the AL-Aqsa mosque and then moved to the top of the seven heavens and reach to the Sedrat AL- Muntaha .The Judges were disagreed and divided to two groups the first said that the prophet was crippled by his spirit and body and others said just by his spirit but not lost his body. Add that they disagreed about Prophet's vision to his lord the first confirm that happened such ( Iben Abbas ) others are refusal that such (Aisha) blessing upon them The prophet ( peace and blessings of Allah be upon him) said to his lord on the night of Israa.